Alternative technology niches and sustainable development: 12 years on. Issue 4 (1st October 2016) - Smith, Adrian
Abstract : This article provides brief, personal reflections on developments in the research fields of sociotechnical transitions theory and grassroots innovation since publication of the article 'Alternative technology niches and sustainable developments'. What is striking about work since then is the importance for sustainable development of interaction and contestation between diverse approaches to innovation. Rather than looking for general models for sustainable innovation, research can fruitfully understand interactions and exclusions between diverse approaches. Undertaken critically and reflexively, such work sheds light on the wider social structures that inhibit a more democratic innovation politics.